ANALISIS EKSPOSUR EKONOMI DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA PADA PERUSAHAAN ROKOK YANG TERCATAT DI BEI - Ida Musdafia Ibrahim; Arif Haryono (Akademi Akuntansi YKPN Yogyakarta, 2018)
This study aims to analyze economic exposures and its factors namely exchange rates and inflation, that influence firm value as reflected through firm cash flow. Analytical method used Ordinary Least Square and eviews as analytical tool. This study used secondary data and cigarette industry companies listed on the Indonesia Stock Exchange as samples along 2008 to 2017. Samples choosing method used purposive sampling based on determined criterias. The results showed that partially economic exposure had positive effects on firm value but insignificant. These could be seen from the economic exposure factors influncenced namely exchange rates and inflations.The exchange rate risk has low influenced cash flow was caused of the tobacco industry has low level of export/import.Enhance,inflation also had low effect on cash flow was caused of the tendency of cigarette consumers will continue to buy cigarettes even though its price increases. In short, economic exposure in the tobacco industry has low influence toward firms value. Hence, simultaneously changes in exchange rates and inflation which are economic exposure indicators have a significant effect on cash flows. Keywords: Economic Exposure, Exchange Rate Risk, Inflation Risk, Firms Value, Cash Flow